Effect of aluminum addition on the properties of CoCuFeNiTi high entropy alloys. (2018) - Sathyanarayana Raju, CH.V.; Venugopal, D.; Srikanth, P.R.; Lokeshwaran, K.; Srinivas, M.; Chary, C.J.; Ashok Kumar, A.
Abstract: This study investigates the effect of aluminum addition on the micro structural, corrosion and mechanical properties of Alx CoCuFeNiTi (x = 0, 0.25, 0.5, 0.75, 1 atom %) High Entropy Alloys which were prepared by Arc melting route. Addition of Al changes the microstructure of the alloys from FCC to a mixture of FCC and BCC phases. The corrosion behavior of the alloys in the 3.5 % NaCl solution and Red Fuming Nitric Acid is reported. Addition of 0.25 atom % Al improves the corrosion resistance of the high entropy alloys in both solutions, whereas higher fraction elevates the corrosion rate.